OBESITY RISK FACTOR FOR MULTIPLE DISEASES HIGH BLOOD PRESSURE - Cojocaru Daniela (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
The aim of this study is to design an effective physical therapy program based on the procedures and means of exercise, along with a proper diet, leading to the elimination of immediate and late complications of obesity. I guess if we apply an early physiotherapy program, respectively exercise and an adequate diet, we will obtain an improvement of the health, helping to eliminate the immediate and late complications of obesity. The study was performed at the USV Swimming and Physiotherapy Complex, having at its disposal specific endowments for the development as efficiently as possible and in favorable conditions for the patient. The research stages are the following: In the first stage - we have established the existing specialized literature that deals with the topic proposed for the study and the case studies of the last years, as well as the way of solving it. Based on the information gathered, we prepared the recovery program. In the second stage - we selected the subject for the study. Also at this stage we chose the necessary tools for evaluation. We prepared the individual file with the data necessary to establish the clinical-functional diagnosis. This sheet was the decision-making basis for setting the goals and treatment program. In the third stage - we applied the kinetotherapeutic treatment programs, specific to the case. In the final stage - I made the final evaluation of the subject and based on the results I appreciated the individual evolution, materialized in the graphic presentation.